Costs and benefits of Internet gambling for society (evidence from the United Kingdom) - Chalaguine, Artur A. (Journal of the Belarusian State University. Economics, 2019)
This study is trying to quantify the costs and benefits of Internet gambling as well as calculate the net effect for the United Kingdom. Therefore, the research aim is to see whether Internet gambling should be a concern in the United Kingdom right now. The costs and benefits are calculated by using generally accepted measures and concepts of welfare economics, which should create consensus regarding a justified framework in the gambling literature, especially in regards to the calculation of social costs. The results show that the net effect of online gambling in the United Kingdom ranges from 643 168 031 to 2 774 780 478 pounds sterling if addicted gamblers are considered rational, while it ranges from 418 791 001 to 2 550 403 448 pounds sterling to if addicted gamblers are considered irrational. Therefore, the total value of the benefits will depend on whether gambling is seen as a rational action or not. Furthermore, the total value of the costs will mainly depend on how the emotional costs of gambling are treated.